2001
DOI: 10.1074/jbc.m102021200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Cystatin A by Keratinocytes Is Positively Regulated via the Ras/MEKK1/MKK7/JNK Signal Transduction Pathway but Negatively Regulated via the Ras/Raf-1/MEK1/ERK Pathway

Abstract: Cystatin A, a cysteine proteinase inhibitor, is a cornified cell envelope constituent expressed in the upper epidermis. We previously reported that a potent protein kinase C activator, 12-O-tetradecanoylphorbol-13-acetate, increases human cystatin A expression by the activation of AP-1 proteins. Here, we delineate the signaling cascade responsible for this regulation. Co-transfection of the cystatin A promoter into normal human keratinocytes together with a dominant active form of ras increased the promoter ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
(60 reference statements)
3
14
0
Order By: Relevance
“…Future studies should focus on identification of such transcriptional repressors that bind to the DNA sequence within dermokine promoter. A previous study has shown that the phosphorylated forms of ERKs were present in the basal cell layer, but totally disappeared in the granular layer of the normal human epidermis [20]. In the present study, we showed that exposure of human keratinocytes to dermokine-b significantly decreased the phosphorylation level of ERK1/2 by 50% compared to control in proliferating culture conditions.…”
Section: Discussionsupporting
confidence: 65%
“…Future studies should focus on identification of such transcriptional repressors that bind to the DNA sequence within dermokine promoter. A previous study has shown that the phosphorylated forms of ERKs were present in the basal cell layer, but totally disappeared in the granular layer of the normal human epidermis [20]. In the present study, we showed that exposure of human keratinocytes to dermokine-b significantly decreased the phosphorylation level of ERK1/2 by 50% compared to control in proliferating culture conditions.…”
Section: Discussionsupporting
confidence: 65%
“…Evidence supporting the involvement of JNK in keratinocyte differentiation derives from the findings of Takahashi et al (10), who have shown by immunohistochemistry on normal human epidermis that the active phosphorylated form of JNK is present in keratinocytes of the upper spinous and granular layers. Moreover, in studies carried out in vitro with cultured normal human keratinocytes, these authors demonstrated that the expression of cystatin A, a key marker of differentiation, requires the activation of JNK (11). Similarly experiments with cultured keratinocytes have also highlighted the importance of p38 MAPK signaling in the terminal differentiation of these epidermal cells.…”
mentioning
confidence: 90%
“…In vitro studies with cultured normal human keratinocytes have clearly demonstrated that JNK, p38, and many of their upstream activators regulate positively the expression of proteins such as involucrin, loricrin, transglutaminase 1, and cystatin A (11,16), which are required during the final stage of the terminal differentiation program. The results presented here show that the MAPKKK DLK preferentially stimulated the JNK subgroup of MAPKs upon expression in poorly differentiated human keratinocytes.…”
Section: Fig 6 Expression Of Dlk In Keratinocytes Induces Late But mentioning
confidence: 99%
See 1 more Smart Citation
“…However, indirect evidence strongly suggests that the proliferative state of basal keratinocytes in human skin crucially depends on the activity of the EGFR-Ras-ERK cascade. For instance, phosphorylated ERK has been detected, via immunohistochemical methods, almost exclusively in the stratum basale, the proliferative compartment of the skin harboring the keratinocyte stem cells (see below) (1,70). Furthermore, abnormally increased phosphorylation of ERK in the stratum spinosum has been observed in cases of psoriasis, a disorder that is characterized by a keratinocyte hyperproliferation in the suprabasal layers (24).…”
mentioning
confidence: 99%